MORPHOMETRIC DISTINCTION OF DOMESTIC AND SYLVATIC POPULATIONS OF Rhodnius ecuadoriensis FROM DIFFERENT GEOGRAPHICAL ORIGINS - Patterson, J S. (2020)
ABSTRACTRhodnius ecuadoriensis (Hemiptera, Reduviidae) is an important vector of both Trypanosoma hemoflagellates, Trypanosoma cruzi and Trypanosoma rangeli, in Ecuador and Peru. Ecotopes of sylvatic and domestic/peridomestic habitats have been reported in Ecuador. Meanwhile in Peru, to the best of our knowledge, findings of sylvatic populations in their different ecosystem regions have not yet been documented. Could this be the product of a lack of appropriate studies on wild populations of triatominae in Peruvian environments? In order to elucidate this topic, we take advantage of new insights in geometric morphometry as a tool to help differentiate between wild populations and the corresponding domestic/peridomestic ones, collected in their respective environments. When analyzing our results, we confirmed the efficacy of this technique in our study, and furthermore, we believe that it could be a proper tool for rangeliosis and Chagas disease vector control surveillance in Ecuador and Peru.Keywords: Morphometric geometry, sylvatic, domestic/peridomiestic populations distinction, Rhodnius ecuadoriensis. RESUMENRhodnius ecuadoriensis (Hemiptera, Reduviidae) es un importante vector de los tripanosomas Trypanosoma cruzi y Trypanosoma rangeli en el Ecuador y Perú. Se han reportado ecotopos de hábitats silvestres y domésticos/peridomésticos en Ecuador. Sin embargo, en Perú, hasta donde sabemos, no se ha documentado hallazgos de dichas poblaciones silvestres. ¿Podría este ser el caso de una falta de estudios focalizados en la búsqueda de poblaciones silvestres de triatominos dentro de los diferentes ecosistemas del Perú? Para elucidar este tema, aplicamos nuevas perspectivas en morfometría geométrica, como una herramienta que podría auxiliar en la diferenciación de poblaciones silvestres de aquellas domésticas/peridomésticas, colectadas en sus respectivos ambientes naturales. Al analizar nuestros resultados, se confirmó la utilidad de esta técnica dentro de nuestro estudio, y esto nos llevó a creer asimismo que serviría como un elemento apropiado en el control vectorial de la enfermedad de Chagas y de la rangeliosis, en Ecuador y Perú.Palabras claves: Geometría morfométrica, silvestre, diferenciación de poblaciones domesticas/peridomesticas, Rhodnius ecuadoriensis.